La literatura infantil y su incidencia en el desarrollo del lenguaje oral de los niños y niñas de primer año de educación general básica de la unidad educativa “Juan Montalvo” de la parroquia de Vilcabamba, periodo 2013- 2014. Lineamientos alternativos - León Jaramillo, Angela Francisca (2015)
This thesis called LA literature children and his incidence in the development of the language ORAL of the children and girls from first year of basic GENERAL education unit educational "JUAN MONTALVO" of the parish of VILCABAMBA, period 2013-2014. ALTERNATIVE guidelines, has been structured and developed according to the regulations of academic regime of the National University of Loja The general goal that guided the research was: analyzing the incidence of children's literature in the development of the Oral language of the children of the first year of basic General education in the educational unit "Juan Montalvo" of the parish of Vilcabamba. The methods used for the preparation of the present research work were: scientist, inductive, deductive, descriptive and statistical model; the survey aimed at teachers to determine the types of children's literature that used in his day of work with the children of the first year of the Basic General education of the educational unit "Juan Montalvo" of the parish of Vilcabamba. And a Test Zimtmerman, on a scale of language pre-school and school skills Verbal-this test will evaluate the development of the Oral language of the children of the first year of basic General education. 4 50% of the surveyed teachers are always activities of children's literature in the daily working day and the other 50% twice a week, as the stories, riddles and songs are which facilitates the motivation in children and gives you the ability to develop and refine their vocabulary in all its expressions. The development of Oral language of the children studied, applied the test of ZIMMERMAN, in which demonstrate that 59% of evaluated children is located at the normal level in the development of Oral language, 29% in level low in Oral language development, and 12% is located in the level excellent in Oral language development.